The Effect of Hadith and Character Education Implementation on Student Discipline in Islamic Schools - Muhammad Abdul Ilah; M. Bahtiar Ubaidillah; Muhammad Rizaq (Westscience Press, 2024)
This study investigates the effect of Hadith and character education implementation on student discipline in Islamic schools. Using a quantitative approach, data were collected from 70 students through a structured questionnaire utilizing a 5-point Likert scale. The analysis, conducted with SPSS version 25, revealed significant positive relationships between Hadith education, character education, and student discipline. Regression analysis showed that both variables significantly predict student discipline, with character education demonstrating a slightly stronger effect. These findings highlight the importance of integrating religious teachings with structured character-building programs to foster disciplined behavior among students. The study provides valuable insights for educators and policymakers to enhance disciplinary practices in Islamic educational institutions.